Role of citizen science in zoological research (Zoological Records and Reviews, 2025)
Citizen science -- the systematic involvement of volunteer non-professional participants in scientific data collection,classification, and analysis -- has emerged as a transformative pillar of modern zoological research, providing spatial andtemporal coverage of animal distributions, population trends, and behavioural ecology at scales that professional surveynetworks cannot match. This review synthesises evidence from 192 primary studies (2005-2025) examining thecontribution, data quality, participant engagement, and policy relevance of citizen science in European zoologicalresearch. We evaluate eight major European citizen science programmes across five performance dimensions -- datavolume, taxonomic coverage, data quality relative to professional surveys, geographic coverage, and policy linkage --and conduct a meta-analysis of 44 paired data quality studies comparing citizen science and professional survey outputs.Mean detection rates in standardised citizen science protocols reach 84.4 +- 6.8% of professional survey referencevalues for birds and 78.4 +- 8.4% for butterflies; occupancy models correcting for imperfect detection reduce this gap tostatistically non-significant differences for 76.4% of species. iNaturalist European records (> 80 million occurrences by2024) have extended documented ranges for 284 invertebrate and plant species and provided first-detection records for48 invasive species in European countries. Structural barriers -- volunteer retention, spatial sampling bias, taxonomicidentification errors, and data standardisation -- are evaluated alongside solutions including automated imageidentification (iNaturalist AI, PlantNet), gamification, and community validation workflows. A framework for integratingcitizen science data into EU Habitats Directive Article 11 surveillance reporting is presented.
Keywords: EU Habitats Directive; biodiversity monitoring; occupancy modelling; species distribution; volunteer engagement; data quality; eBird; iNaturalist; zoological research; citizen science